SOULDER PARESIS DUE TO HERPES ZOSTER NEURITIS: A CASE REPORT - Canan Tıkız; Hatice Mavioğlu; Timur Pırıldar; Çiğdem Tüzün (Archives of Rheumatology, 2005)
In this case report, a patient with the diagnosis of segmental motor paresis (SMP) following herpes zoster (HZ) infection which involved C5-6 roots was presented. The muscle weakness was prominent at the muscles of the right shoulder and his daily activities were significantly restricted. Electrophysiological study revealed neuritis in the upper brachial plexus. After application of physical rehabilitation, significant improvement was observed in symptoms and electrophysiological findings. Our aim to present this case is to review the literature published until now in this regard and to emphasize that post-herpetic neuritis may involve in the etiology of shoulder disorders.